ANTIBIOFILM EFFECTS of Citrus limonum and Zingiber officinale Oils on BIOFILM FORMATION of Klebsiella ornithinolytica, Klebsiella oxytoca and Klebsiella terrigena SPECIES - Avcioglu, Nermin Hande; Sahal, Gulcan; Bilkay, Isil Seyis (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Microbial cells growing in biofilms, play a huge role in the spread of antimicrobial resistance. In this study, biofilmformation of Klebsiella strains belonging to 3 different Klebsiella species (K. ornithinolytica, K. oxytoca and K. terrigena),cooccurences’ effect on biofilm formation amount and anti-biofilm effects of Citrus limon and Zingiber officinale essential oils onbiofilm formations of highest biofilm forming K. ornithinolytica, K. oxytoca and K. terrigena strains were determined.Materials and Methods: Anti-biofilm effects of Citrus limon and Zingiber officinale essential oils on biofilm formations of highestbiofilm forming K. ornithinolytica, K. oxytoca and K. terrigena strains were investigated.Results: 57% of K. ornithinolytica strains and 50% of K. oxytoca strains were found as Strong Biofilm Forming (SBF), there wasn’tany SBF strain in K. terrigena species. In addition to this, clinical materials of urine and sperm were found as the most frequentclinical materials for strong biofilm forming K. ornithinolytica and K. oxytoca isolations respectively (63%; 100%) Secondly, allK. ornithinolytica strains isolated from surgical intensive care unit and all K. oxytoca strains isolated from service units of urologywere found as SBF. Apart from these, although the amount of biofilm, formed by co-occurence of K. ornithinolytica - K. oxytocaand K. oxytoca - K. terrigena were more than the amount of biofilm formed by themselves separately, biofilm formation amount ofco-occurrence of K. ornitholytica - K. terrigena strains was lower than biofilm formation amount of K. ornithinolytica but higherthan biofilm formation amount of K. terrigena.Conclusion: The antibiofilm effects of Citrus limonum and Zingiber officinale essential oils could be used against biofilmKlebsiella aquired infections.